2.45-GHz Microwave Radiation Impairs Hippocampal Learning and Spatial Memory: Involvement of Local Stress Mechanism-Induced Suppression of iGluR/ERK/ CREB Signaling - Shahin, Saba; Banerjee, Somanshu; Swarup, Vivek; Singh, Surya Pal; Chaturvedi, Chandra Mohini (Oxford University Press, 2018)
Microwave (MW) radiation induced oxidative stress reduces dendritic arborization, spine density and number of hippocampal pyramidal neurons and hence, impair learning and spatial memory through p53-dependent/independent apoptosis of hippocampal neuronal and nonneuronal cells. However, the mechanisms responsible for MW radiation induced impairment in memory formation remains still unknown. This study elucidates the effect of short (15 days) and long-term (30 and 60 days) low level 2.45 GHz MW radiation-induced local stress on the hippocampal spatial memory formation pathway in adult male mice. Twelve-weeks old mice were exposed to 2.45 GHz MW radiation (continuous-wave with overall average Power density of 0.0248 mW/cm2 and overall average whole body SAR value of 0.0146 W/Kg) @ 2 h/d for 15, 30, and 60 days. Learning and spatial memory was assessed by 8-arm radial maze. We have investigated the alterations in serum corticosterone level and the expression of glucocorticoid receptor, corticotropin-releasing hormone (CRH), inducible nitric oxide synthase (i-NOS), iGluRs, PSD-95-neuronal NOS (n-NOS) system, protein kinase A, protein kinase CeERK1/2-pERK1/2 in all the hippocampal subregions, viz. CA1, CA2, CA3, and DG through immunohistochemistry/ immunofluorescence and alterations in the expression of hippocampal glucocorticoid receptor, CRH-receptor 1 (CRH-R1), cAMP-response element-binding (CREB), and phosphorylated-CREB (p-CREB) through western blot analysis. We observed that 2.45 GHz MW irradiated mice showed slow learning and significantly increased number of working and reference memory errors in radial maze task. Further, 2.45 GHz MW radiation exposure increases serum corticosterone level and the expression of CRH, CRH-R1, and i-NOS, while the expression of iGluRs, n-NOS, PSD-95, protein kinase Ce, protein kinase A, ERK-p-ERK, CREB, and p-CREB decreases in above mentioned hippocampal subregions in a duration dependent manner. Our findings led us to conclude that 2.45 GHz MW radiation exposure induced local stress suppresses signaling mechanism(s) of hippocampal memory formation
Keywords: Glutamate receptors; Hippocampal stress; Learning and memory formation; Microwave radiation; PSD-95; Signaling molecules